UPAYA MEDIASI DALAM PENYELESAIAN SENGKETA DI LEMBAGA PERBANKAN - Suherman, Suherman (Jurnal Yuridis, 2017)
In many countries the use of mediation as a method of dispute settlement was initially voluntary. The banking dispute that begins with a costumer?s complaint against the services of a bank which is not responded, will cause a dispute. The banking dispute can also occur due to contractual relationship between bank and debtor. There is several action that can be done by debtor for doing banking mediation, namely debtor has meeting with bank party to ask explanation for mediation, if acknowledge and understand so debtor can propose a mediation process to the implementation of banking mediation function, the debtor follows the mediation process and put it into an agreement. In this case, author also describe the benefits and weakness about banking mediation.